Healthcare Financing in Low and Middle-Income Countries and Achieving Universal Health Coverage - Amadou Boubacar (Resolusi: Jurnal Sosial Politik, 2021)
Using a comparative healthcare system approach, this paper discusses the existing healthcare financing methods in low-and middle-income countries in the move towards achieving universal health coverage (UHC). The article finds that traditional channels of financing the health sector in these countries include government’s budget, donors’ aid, national health insurance, and out-of-pocket model. Moreover, the paper explores other alternative mechanisms for raising resources for the health sector including tax on demerit goods, remittances, and sovereign wealth funds’ revenues. This paper is of particular interest to policymakers in low-and middle-income countries targeting to achieve UHC.